Determinants of Mandatory Disclosure for Local Government Financial Statements - Muawanah, Afifah; Ermawati (Journal of Economics and Behavioral Studies, 2022)
This study sought to objectively investigate the impact of local government financial disclosure levels on the amount of income in the municipality, general allocation fund, number of local parliaments, and human development index (LKPD). All financial accounts from local governments in Indonesia make up the study’s population. 455 district/city administrations across the island of Sumatra were used as the purposive selection sample for this study from 2017 to 2019. In this work, multiple linear regression analysis with STATA version 16 is used for hypothesis testing. The level of disclosure of LKPD is unaffected by the income level of the municipality or general allocation funds, according to the examination of the data. While having an impact on the level of disclosure of local government financial statements (LKPD) are the number of local parliaments and the human development index. This study offers data on variables that will impact the amount of disclosure in financial statements for local governments. A higher level of disclosure will signify that local governments are managing their finances with a high degree of accountability and openness.